2009
DOI: 10.1111/j.1600-079x.2009.00684.x
|View full text |Cite
|
Sign up to set email alerts
|

Membrane‐bound melatonin receptor MT1 down‐regulates estrogen responsive genes in breast cancer cells

Abstract: Melatonin possesses anti-estrogenic effects on estrogen receptor expressing (ER+) breast cancer cells in culture by reducing cell cycle progression and cell proliferation. There is increasing agreement that on a cellular level the effects of melatonin are primarily induced by the membrane-bound receptor MT1. The participation of a second, nuclear receptor of the group of ligand-dependent transcription factors, called RZRalpha, is under debate. In this study we used a number of breast cancer cell lines differin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 28 publications
3
54
0
Order By: Relevance
“…Extrapineal sites contribute poorly, or only upon specific stimuli to circulating melatonin [1]. Melatonin influences numerous physiological actions that may be mediated by the binding of the indoleamine to membrane receptors in all tissues [2,3]. Due to its excellent lipophilic properties, melatonin is able to enter the subcellular compartment, finding it in high concentrations in the nucleus and the mitochondria of cells [4,5], being capable to bind to some cytosolic proteins like kinase-C [6], calmodulin [7] and calreticulin [8].…”
Section: Introductionmentioning
confidence: 99%
“…Extrapineal sites contribute poorly, or only upon specific stimuli to circulating melatonin [1]. Melatonin influences numerous physiological actions that may be mediated by the binding of the indoleamine to membrane receptors in all tissues [2,3]. Due to its excellent lipophilic properties, melatonin is able to enter the subcellular compartment, finding it in high concentrations in the nucleus and the mitochondria of cells [4,5], being capable to bind to some cytosolic proteins like kinase-C [6], calmodulin [7] and calreticulin [8].…”
Section: Introductionmentioning
confidence: 99%
“…Since Ca 2 þ seems to be a crucial regulator of the cell cycle necessary for proper proliferation (Bertolesi et al, 2002;Gray et al, 2004;Naziroğlu et al, 2012;Wang et al, 2000), the associated reduction of free [Ca 2 þ ] i observed in our experiments supports the clue that melatonin may contribute to the decline of proliferation also disturbing internal Ca 2 þ homeostasis. The G-protein-coupled melatonin MT1 receptors are expressed in MCF-7 cells (Girgert et al, 2009;Hill et al, 2011b;Jablonska et al, 2013;Jawed et al, 2007;Rich et al, 1999) and, via the inhibition of adenylate cyclase activity (Jablonska et al, 2013;Jawed et al, 2007), their activation leads to the decrease of adenosine 3 0 , 5 0 -cyclic monophosphate (cAMP) synthesis. Considering that in MCF-7 melatonin affected cell functionality by a significant depletion of ATP levels (Margheri et al, 2012), we propose that the decrease of cAMP, leading to a decrease of PKA activity and channel phosphorylation, can be considered a crucial mechanism involved in the reduction of L-and T-type Ca 2 þ currents (Mahapatra et al, 2012;Novara et al, 2004;Sundelacruz et al, 2009), further stressing the evidence that Ca 2 þ channels are a target by which melatonin can modulate cell proliferation.…”
Section: Ctrmentioning
confidence: 99%
“…Moreover, preclinical in vitro and in vivo studies and clinical trials showed that melatonin was able to exert an oncostatic action on different tumors (Girgert et al, 2009;Hill et al, 2009Hill et al, , 2011aJung and Ahmad, 2006;Sánchez-Barceló et al, 2012;Srinivasan et al, 2008), to increase the efficacy of chemotherapy when used in adjuvant settings and to decrease the side effects (Vijayalaxmi et al, 2002). Since proliferation and differentiation are typical of any cell system and are carefully regulated in the course of physiological development and life cycle, tumor evolution must imply a deregulation of their morphofunctional features.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We were able to show that the breast cancer susceptibility gene BRCA-1 is a good candidate to study cross-talk between ER and melatonin signal transduction [Girgert et al, 2009]. BRCA-1 expression is upregulated by estradiol, because the BRCA-1 promoter contains an AP-1 instead of an estrogen receptor element [Webb et al, 1999].…”
Section: Introductionmentioning
confidence: 99%